A Non‐Column Based, Fully Unstructured Implementation of Kessler's Microphysics With Warm Rain Using Continuous and Discontinuous Spectral Elements. (18th March 2023) - Tissaoui, Yassine; Marras, Simone; Quaini, Annalisa; de Brangaca Alves, Felipe A. V.; Giraldo, Francis X.
Abstract: Numerical weather prediction is pushing the envelope of grid resolution at local and global scales alike. Aiming to model topography with higher precision, a handful of articles introduced unstructured vertical grids and tested them for dry atmospheres. The next step toward effective high‐resolution unstructured grids for atmospheric modeling requires that also microphysics is independent of any vertical columns, in contrast to what is ubiquitous across operational and research models. In this paper, we present a non‐column based continuous and discontinuous spectral element implementation of Kessler's microphysics with warm rain. We test the proposed algorithm against standard three‐dimensional benchmarks for precipitating clouds and show that the results are comparable with those presented in the literature across all of the tested effective resolutions. While presented for both continuous and discontinuous spectral elements in this paper, the method that we propose can be adapted to any numerical method used in other codes, as long as the code can already handle vertically unstructured grids. Plain Language Summary: The earth climate is warming faster than ever. While climate models are the tool available to scientists to forecast its future evolution, they are biased by uncertainties that are, arguably, mostly embedded in the modeling of clouds. Thanks to the advent of exascale computing, a reduction of cloud modeling uncertainties can be expected by simulating clouds at higher and higher resolutions. While uniform high resolution across the whole domain is ideal, for computational efficiency reasons scientists are likely to increase the model resolution in some regions more than others not only in the horizontal direction—which is a standard approach—but also along the vertical direction. Grid refinement in the vertical direction, however, may lead to the loss of the vertical structure of the grid columns, affecting the usability of column‐based physics packages that are used to model clouds and precipitation. To overcome this problem, we present an algorithm to solve the equations that model precipitating clouds along arbitrarily shaped grids in any spatial direction. This approach is advantageous from a modeling perspective as well as from a computational one because it allows full flexibility of the domain partitioning algorithms when hundreds of thousands of parallel processors are used. Key Points: A non‐column based spectral element approach to model precipitating clouds is presented The approach can be easily applied to any microphysics scheme with and without precipitation This approach will make full physics simulations of the atmosphere on unstructured grids possible